2014
DOI: 10.1177/0148607114529161
|View full text |Cite
|
Sign up to set email alerts
|

Computer‐Based Malnutrition Risk Calculation May Enhance the Ability to Identify Pediatric Patients at Malnutrition‐Related Risk for Unfavorable Outcome

Abstract: PeDiSMART, applicable to the full age range of patients hospitalized in pediatric departments, graded according to BIA PhA, and embeddable in medical electronic records, enhances efficacy and reproducibility in identifying pediatric patients at malnutrition-related risk for an unfavorable outcome. Patient allocation according to the PeDiSMART score on admission is associated with clinical outcome measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 21 publications
(53 reference statements)
0
25
0
8
Order By: Relevance
“…This tool has high sensitivity and specificity for predicting weight loss and the need of nutritional support during hospital stay, but it has moderate inter-interviewer agreement (κ = 0.474) [41].…”
Section: Nutritional Screening Tools For Pediatric Patientsmentioning
confidence: 99%
“…This tool has high sensitivity and specificity for predicting weight loss and the need of nutritional support during hospital stay, but it has moderate inter-interviewer agreement (κ = 0.474) [41].…”
Section: Nutritional Screening Tools For Pediatric Patientsmentioning
confidence: 99%
“…Table 2 compiles and integrates the information from the 15 studies included in the literature review according to the PICO characteristics of the research. [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] It should be noted that, although the search included original studies published between 2002 and 2017, the selected articles were released between 2010 and 2017 (67% of them were published between 2012 and 2017), thus indicating that the results are up-to-date. All studies were developed in European countries.…”
Section: Search Resultsmentioning
confidence: 99%
“…The remaining 8 studies were classified at a moderate level since they were multicenter studies, with randomized, systematized or consecutive sampling and generally consistent results that allow, to some extent, the generalization of findings to clinical practice. [28][29][30][31]33,35,38,40 Recommendations for the use of nutritional screening tools in pediatrics Of the seven tools identified in this systematic review, quality assessment was only possible in six of them, namely, PYMS, iPYMS, STAMP, PMST, STRONGkids and PEDISMART. A complete quality analysis -i.e.…”
Section: Levels Of Certainty Of the Studiesmentioning
confidence: 99%
“…Moreover, adverse impacts of malnutrition and the influence of an underlying disease on nutritional status interact and both affect LOS. When LOS as an outcome measure was controlled for confounders in the Paediatric Digital Scaled MAlnutrition Risk Screening Tool (PeDiSMART) validation study, 18 it was found not to be significantly associated with nutritional risks.…”
Section: Discussionmentioning
confidence: 98%